PENGARUH PESAN VISUAL KOMUNITAS GEAR FIGHT INDONESIA TERHADAP TINGKAT LOYALITAS MAINAN CRUSH GEAR DI FACEBOOK - Arazu, Harits; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The development of communication technology everybody can answer their needs by lot of media such as Facebook. Gear Fight Indonesia community focused to crush gear toys hobby on Facebook can solved their needs. Rely on visual message to communicate they made a influence that successfull grew the loyalty to crush gear toys in Gear Fight Indonesia community. Theory of loyalty level supported to this study, generally this theory described category of loyalty levels consumer based to the grades when consume a product or service. The loyalty to products or service came if it can filled a satisfaction and also solve to consumer needs. On the point be the purpose of this study, to count the influence about visual messsage of Gear Fight Indonesia community with loyalty level of crush gear toys on Facebook.This study used descriptive quantitative method. Data collection techniques in this study using a questionnaire spread online by Google form. The number of samples for this study was 96 respondents and using quote sampling techniques. To determine the influence of these two variables, the researchers will use a simple linear regression analysis. And for the process of calibration questionnaire test, was performed by using the program Statistics Product And Service Solutions (SPSS) version 20 of Windows.Based on these results with indicators of variables visual message such as pictures and video, and also variable of loyalty level such as no loyalty, latent loyaty, inertia loyalty, and last premium loyalty. It will be obtained by the regression coefficient in this study is Y = 0,865 + 0,012 X which are significance level was 0.01 smaller than α = 0.05. Therefore, Ha was accepted and Ho was rejected, it means that there is the influence of visual message variable to variable of loyalty level with a contribution of 73.5% strong category. The percentage was explained that it have strong influence between visual message and loyalty level of crush gear toys in Gear Fight Indonesia Community on Facebook. Meanwhile the balance of this study is 26.5% which influenced by another variable where not including into this study.Key Words: Visual message, Loyalty, Loyalty levels theory